Assessment of the Role of Christian Missionaries in the Educational Transformation of Rumuruti Sub-County of Laikipia County, Kenya, 1890-2010 - Kinya Rita Majau; Mwaruvie John; Kavulavu Leen, (African Journal of Education,Science and Technology (AJEST), 2025)
Christian missionaries in Rumuruti Sub-county of Laikipia County, Kenya played a pioneer role in the educational transformation of the community. Despite initial hostile resistance from the community, the missionary effort slowly but surely gained ground and left a great mark in the society. The region was largely inaccessible and far off from the main settlement area of Nyahururu, which was the centre of white settler farms in Laikipia County. The missionaries introduced formal education in the Sub-county, which has had tremendous impact on the local people. The objective of this study is to examine the role of Christian missionaries in the educational transformation of Rumuruti Sub County of Laikipia County, Kenya. The study adopted a historical research design. The study was informed by Modernization theory. The theory postulates that changes occur when a traditional society adopts modern technological and social practices of an advanced society. The study used purposive sampling technique in selecting the sample size of 100 respondents who were knowledgeable about mission work in Rumuruti Sub-county. Primary data was collected by use of questionnaires and interview schedules. In addition, data was accessed from the Kenya National Archives and Documentation Centre in Nairobi and Church Mission Archives. The study findings demonstrate that Christian Missionaries have contributed to educational transformation of Rumuruti Sub County. The findings of the study enrich the historiography of missionary activities in Kenya.